Omnibus Law: Government's Solution To Overcome Hyper Regulation A Review Of State Law - Hadi, Abdul; Yusdiansyah, Efik; Santoso, Bambang (University of Merdeka Malang, 2024)
Indonesia is the country with the most regulation (hyper regulation) in the world when compared to several large countries such as the United States, Germany and England. Hyper regulation that occurs in Indonesia will cause regulations in Indonesia to malfunction and become a threat, this is because these regulations will overlap, entangle each other. The Hyper Regulation that is occurring in Indonesia can be overcome, one way is to revise the statutory regulations, however implementing this conventional revision will take a very long time to carry out harmonization and synchronization. The omnibus law method is the government's solution to overcome hyper regulation and create harmonization of regulations. The research method used is a normative juridical research method with descriptive analytical research specifications. The result of this research is the question of whether the omnibus law method can be the main solution in solving the problem of hyper regulation that occurs in Indonesia and really provide benefits or even cause more problems and losses, depending on how wise and mature the policy makers are in reviewing it. various perspectives. Because this omnibus law is very complex because it requires an in-depth study of the many regulations that will be changed, revoked and/or combined.